Síntese de catalisador magnético (CaO/Fe3O4) e seu desempenho na produção de biodiesel via rota metílica - Guedes, Gerson Barbosa (2021)
Global warming and environmental pollution have motivated researchers in the search for renewable energy sources to replace fossil fuels. Biofuels have been identified as an alternative capable of minimizing environmental impacts. Among the biofuels, biodiesel stands out for being biodegradable, free sulfur and aromatics. In this context, the work aimed at the synthesis of heterogeneous calcium oxide (CaO) catalysts supported on magnetite (Fe3O4) to obtain biodiesel through transesterification o methyl of soybean oil. The synthesis of the magnetic support (Fe3O4) was made by coprecipitation, where the catalysts containing 5, 10, 15 and 20 % CaO were obtained through wet impregnation with the magnetic support, followed by calcination at 550 °C for 1h. The catalysts were characterized by DRX, EDX, Textural analysis by physical adsorption of N2, TG/DTG, SEM and magnetic force. The chemical composition of the catalyst, by (EDX), confirmed the occurrence, of the CaO and Fe3O4 phases. The XRD showed the formation of the single phase Fe3O4 for the CaO/ Fe3O4 system at 5 %, whereas for the CaO/ Fe3O4 systems at 10, 15 and 20 %, traces of the CaO and Ca(OH)2 phases were observed. The catalysts of 5, 10 and 15 % presented crystallite size and particle diameter of 11.85 and 24 nm; 10.51 and 61 nm; 10.50 and 20 nm, respectively. From the textural analysis by physical adsorption of N2, the formation of mesoporous material was verified, with an increase in the surface area for samples with a higher percentage of CaO. The results of magnetic force showed that increasing the amount of Fe3O4 produces an increase in magnetic force, which proves that reliable magnetic results can be obtained using a configuration relatively simple experimental. The process of synthesis and wet impregnation was satisfactory in the production of the catalyst. The Biodiesel was obtained from soybean oil, using a parr reactor, using the methyl route. The best results obtained through gas chromatography (GC) of the reaction products in methyl ester content were 87.98 % for the pure CaO catalyst with 5h reaction, and for the catalyst impregnated with CaO20%/Fe3O4 it was 31.96 %. The reaction products were also characterized by kinematic viscosity.